Criação e exploração de uma infra-estrutura de informação geográfica em Timor-Leste - Matos, João (Finisterra, 2003)
SETTING UP AND EXPLORING GEOGRAPHIC INFORMATION INFRASTRUCTURES IN EAST TIMOR. This paper presents a report on the production and usage of Geographic Information applied in a co-operation project with Timor Leste. The project was funded by the Portuguese Government, developed by technical teams of the Technical University of Lisbon and coordinated by the group GERTiL. The work in the project resorted extensively to geographical information. The article describes the global implementation strategy, namely the definition of a co-ordinate system, the installation of a GPS permanent base-station, field surveys, remote sensing and data gathering. Different projects made use of the built infrastructure, namely a strategic development plan, the “school mapping” project, the border demarcation and other smaller projects.